Psychological Effects and Associated Factors of Examination Stress among School Children - Murali Mohan; Deepthi Saligram (CV. Doki Course and Training, 2026)
Examination stress represents a critical psychological concern among school-going children, significantly influencing emotional well-being, academic performance, and overall developmental outcomes. The present study aimed to assess the psychological effects of examination stress and identify associated factors among students aged 10–18 years. A cross-sectional descriptive design was employed, involving a sample of 300 students from rural and semi-urban schools in Kolar district, Karnataka. Standardized instruments, including the Examination Stress Scale (ESS) and the Depression Anxiety Stress Scales (DASS-21), were utilized to measure stress and related psychological outcomes. The findings revealed that approximately 62% of students experienced moderate to high levels of examination stress. Significant positive correlations were observed between examination stress and anxiety (r = .61, p < .001) as well as depression (r = .54, p < .001), indicating a strong association between academic stress and psychological distress. Furthermore, multiple regression analysis identified key predictors of examination stress, including high parental pressure, poor sleep quality, and excessive screen time. These findings underscore the substantial psychological burden associated with academic examinations among adolescents, particularly in competitive educational contexts. The study highlights the urgent need for implementing school-based mental health interventions, promoting adaptive coping strategies, and addressing environmental stressors such as parental expectations and lifestyle factors. Additionally, policy-level reforms aimed at reducing academic pressure and integrating mental health services within educational systems are recommended to support the well-being and holistic development of students.